Comparison of perceptions of wellness tourism in Korea before and after COVID-19: Results of social big data analysis - Jang Heon Han; Kab Soo An (Global Business & Finance Review (GBFR), 2022)
Purpose: This study explored strategies aimed at revitalizing wellness tourism in the post-coronavirus 2019 (COVID-19) era, and investigated consumer perceptions of wellness tourism before and after the outbreak of COVID-19. Design/methodology/approach: Keywords pertaining to wellness tourism were extracted from social media platforms, such as Naver, Daum, and the social network service (SNS) Facebook, as well as from the search engine Google. Text mining, frequency analysis, centrality analysis, and CONCOR analysis were conducted on the extracted keywords. The study period was divided into pre- and post-COVID-19 outbreak periods (4,984 and 4,360 keywords, respectively). In total, 100 and 50 searches were analyzed in the pre- and post-outbreak periods, respectively. Findings: Prior to the outbreak, awareness of wellness tourism and programs appear to have been high, while after the outbreak specific wellness tourism destinations, including Jeju and Gangwon, were recognized. In addition, the desire for healing of both body and mind appeared to be greater after the outbreak. Research limitations/implications: In the post-COVID era, local governments and policymakers will need to develop programs to boost local wellness tourism. Advertising and promotion on online social media platforms and SNS, emphasizing the positive effects of wellness tourism such as healing and meditation, could further increase the number of visitors to these destinations. Comparative research on wellness tourism in different countries will also be important, as perceptions of COVID-19 may vary among various countries such as Korea, Japan, and China. Originality/value: In the past, wellness tourism studies focused on research topics such as tourism development and tourism motivation, but this study resulted in the expansion of the research by applying the social media big data analysis method, which has recently attracted attention in the hospitality industry.
Keywords: 650; Wellness tourism; COVID-19; Social media big data; Social network analysis; Semantic network analysis